2019
DOI: 10.1177/0301574219868551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orthodontic Treatment With Straight-Wire Appliance on the Incidence of Temporomandibular Disorders—A 3-Year Cohort Study

Abstract: Introduction: A change in occlusion during orthodontic treatment can affect muscles and joints surrounding the jaw, resulting in temporomandibular disorders (TMD). The aim of this study was to determine the effect of orthodontic treatment with straight-wire appliance on the incidence of TMD in young adults. Materials and Methods: A cohort study was carried out involving 177 adult patients (91 in the treatment group and 86 in the control group). Fonseca’s questionnaire was used for TMD evaluation for all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Nonetheless, a recent systematic review and meta‐analysis 16 suggested a potential association between orthodontic treatment and TMDs. However, this claim should be interpreted with caution considering the limited number of six publications included, 13,18,38–41 each with different criteria for diagnosing TMD and a moderate level of heterogeneity ( I 2 = 53%) 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, a recent systematic review and meta‐analysis 16 suggested a potential association between orthodontic treatment and TMDs. However, this claim should be interpreted with caution considering the limited number of six publications included, 13,18,38–41 each with different criteria for diagnosing TMD and a moderate level of heterogeneity ( I 2 = 53%) 16 …”
Section: Discussionmentioning
confidence: 99%
“…17,18,[35][36][37] Nonetheless, a recent systematic review and meta-analysis 16 suggested a potential association between orthodontic treatment and TMDs. However, this claim should be interpreted with caution considering the limited number of six publications included, 13,18,[38][39][40][41] each with different criteria for diagnosing TMD and a moderate level of heterogeneity (I 2 = 53%). 16 The orthodontic sample was divided into 'maxillary orthodontic treatment' and 'mandibular orthodontic treatment' since a single arch orthodontic treatment may reflect a mild malocclusion and no need for intermaxillary elastics.…”
Section: Tmds and Orthodontic Treatmentmentioning
confidence: 99%
“…In contrast, a cohort study by Jeelani et al . ( 21 ), reported that there was no significant risk of developing TMD with orthodontic treatment (OR=0.73). However, they emphasized that the occlusal relationships achieved at the end of orthodontic treatment did not remain the same, with a lower degree of relapse.…”
Section: Discussionmentioning
confidence: 99%